Ground support technology for highly stressed excavations : integrated theoretical, laboratory, and field research /: integrated theoretical, laboratory, and field research. (2023) - Villaescusa, Ernesto; Thompson, Alan; Player, John; Windsor, Christopher R
No abstract available